Cleaning Ability of Gentlefile Rotary System Compared with Three Alternative Brands - Abdollahi, Amir Ardalan; GhotbiRad, Farough; Amani, Roya; Saadat, Mohammad (Iranian Endodontic Journal, 2024)
Introduction: In this study, the cleaning ability of a stainless-steel rotary instrument called Gentlefile, was compared with three nickel-titanium rotary instruments. Materials and Methods: In this in vitro study, forty mandibular single-rooted premolars were randomly assorted into four groups: Gentlefile, ProTper Universal, RaCe files, and XP-Endo Finisher/ProTaper Universal system (n=10). Final instrumentation was done using the aforementioned files with 5.25% sodium hypochlorite and normal saline for root canal irrigation. Debris and smear layers were observed by the scanning electron microscope on the canal walls in the coronal, middle, and apical third of the root level, through a 4-point scoring system. The chi-square test and Kruskal-Wallis were used for data analysis. Results: The Gentlefile demonstrated a promising outcome in smear layer clearance and debris removal compared with the other three rotary systems (P<0.05), specifically at the apical third of the root canal. Based on chi-square test results, there was a significant relationship between root canal cleaning (three levels of cleanliness) in ProTaper Universal (P=0.004) and Gentlefile (P=0.04) groups. Neither of the investigated systems achieved complete cleanliness. Conclusion: The Gentlefile rotary system can be capable of cleaning the apical third of root canals more than the other three groups including Protaper Universal, RaCe, and XP-Endo Finisher.